Surplus-Sharing Local Games in Dynamic Exchange Processes - Tulkens, Henry; Zamir, Shmuel (Review of Economic Studies, 1979)
Journal Article Surplus-sharing Local Games in Dynamic Exchange Processes Get access Henry Tulkens, Henry Tulkens CORE, Université Catholique de Louvain Search for other works by this author on: Oxford Academic Google Scholar Shmuel Zamir Shmuel Zamir Hebrew University of Jeruslaem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 46, Issue 2, April 1979, Pages 305–313, https://doi.org/10.2307/2297053 Published: 01 April 1979 Article history Received: 01 May 1976 Accepted: 01 April 1978 Published: 01 April 1979